MEMAKSIMALKAN PARTISIPASI MASYARAKAT DAN AKADEMISI DALAM UPAYA MENINGKATKAN STANDAR LAYANAN PAUD - Ningsih, Erna (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of this research is to know the effort of PAUD institution institution to maximize the participation of the society and the academics become part of the effort to improve the service of Early Childhood Education. This research was conducted at TK Negeri Pembina 1 Palembang. This research is qualitative descriptive research. The process of data collection and data mining using observation methods, interviews, documentation and literature review. Data analysis using qualitative descriptive data analysis techniques. The results of research, namely 1) in the preparation of TK Negeri Pembina 1 palembang program includes academics consisting of UNSRI students and UNJ students to provide studies and suggestions and feedback on the designed service program; 2) the community, especially the parents of children involved in parenting, is always emphasized to be an important part in the success of the early childhood program by continuing the program of Early Childhood Education in the family environment; 3) The community, especially the parents of the children, is always involved in the activities of perenting, both as resource persons and as participants; and 4) through collaboration with Puskesmas, parents are trained in the form of family education services how to provide good care and nutritional intake to the child. the participation of parents, community, and academia can further maximize the service standards instituted in Early Childhood Education in TK Negeri Pembina 1 Palembang, both on the aspect of education services, the aspects of care services and nutrition services aspects in early childhood, especially in the city of Palembang.